Meaningful work of thai workers in urban society: A grounded theory - Chaolertseree, Suthasinee; Taephant, Nattasuda (Kasetsart Journal of Social Sciences, 2023)
Massive workplace challenges precipitated by the digital age have given rise to questions about work and its meaning to life. This has become significant interest, involving multidisciplinary studies. The present study extends the literature on meaningful work (MFW) theory by examining the MFW process of urban workers in Thailand. In-person semi-structured interviews were conducted serially, to the point of theoretical saturation, with 15 participants working in the metropolitan area. The data were collected, transcribed verbatim, and then analyzed using the constructivist grounded theory approach. The findings suggest four main themes: (1) the intrapersonal process; (2) environments that foster MFW; (3) MFW outcomes; and (4) workplace challenges. The process essentially begins with an intrapersonal process, and then continues to interact dynamically with the other three themes, each of which fosters the process. The implications of the findings and future directions are discussed.